-(v-7)+1=2-7v

Simple and best practice solution for -(v-7)+1=2-7v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(v-7)+1=2-7v equation:


-(v-7)+1=2-7v

We simplify the equation to the form, which is simple to understand
-(v-7)+1=2-7v

Remove unnecessary parentheses
-1v+7+1=2-7v

We move all terms containing v to the left and all other terms to the right.
-1v+7v=+2-7-1

We simplify left and right side of the equation.
+6v=-6

We divide both sides of the equation by 6 to get v.
v=-1

See similar equations:

| 2a^2=-15a-28 | | 12s+13=35 | | 5x+33=23 | | 240x=12 | | y=-1454(24)+27436 | | -a+20=-3(8a+1) | | 5b+6=-19 | | -6(4+7x)=-4x-24 | | 66=9x-60+(-3x) | | 3x^2-21x+17=0 | | 5y=2x+b | | 2b^2+12b=-18 | | -5(7x+4)=-405 | | -2+5x=-14 | | 75-3x=12-10x | | 3-6x=x+78 | | 4x^3+21x^2-18x-7=0 | | -6x+10-7x=140 | | -2(1-6x)=-2+8x | | -4(-7-5x)=-52 | | y^2+x+10y+26=0 | | f(-x)=8x-8 | | 3(2x-5)+4=35 | | 6x^2+3x-63= | | y=x^6-7x^4-14x^2-x-5 | | 11x=-6x^2+35 | | -3(4a-5)=36-5a | | Y=-143.3(8)+1823.3(8)+6820 | | -33a-10=-7a^2 | | .6x+6=10 | | 1-3x=x-35 | | 3x^2-5x^4-5= |

Equations solver categories